Beating the invader leaflet, 1941 (1941)
1941 1939-1945 "Beating the invader leaflet, 1941" [HFR0066], 1941 Message from the Prime Minister, Winston Churchill, and issued by the Ministry of Information in May 1941 regarding the possible invasion of Great Britain.